The small smart city: renewable energy sources in little town of Italy - Fistola, Romano; Gaglione, Federica; Zingariello, Ida (TeMA - Journal of Land Use, Mobility and Environment, 2023)
The topic of energy has burst into the international and national scientific debate. Urban systems have taken on a fundamental role in having to support technological progress aimed at increasing renewable energy sources such as wind power. On the one hand, the scientific community has concentrated its studies on optimization models to support the energy organization of territorial contexts and on the other, on identifying optimal strategies within complex management systems. In turn, many efforts have also been made in the development of support tools for the improvement of urban energy systems to support decision-making processes. Wind energy is a valid option to improve the economic conditions in the region and reduce the environmental impact, even if the regulatory framework, especially in Italy, has shown structural deficiencies. In this direction, the work takes its cue from a scientific technical consultancy of the Department of Engineering of the University of Sannio and of the Department of Civil, Environmental, Land, Construction and Chemistry Engineering of the Polytechnic of Bari in support of the technical office of the municipality of Biccari (FG) in the definition of the guidelines for the drafting of the General Urban Plan.